USING MASS MEDIA IN TEACHING LISTENING AT THE UNIVERSITY (American Journal of Research in Humanities and Social Sciences, 2025)
The use of mass media in teaching listening at the university level has become an essential component of modern education. This paper explores the effectiveness of incorporating mass media—such as television, radio, podcasts, and digital platforms—into listening comprehension exercises. The study highlights how these resources enhance students' engagement, improve their ability to understand different accents and speech patterns, and expose them to authentic language use. Special attention is given to the role of multimedia in creating an immersive learning environment. The research also discusses potential challenges, including the selection of appropriate media content and the need for structured listening activities. By examining current trends and pedagogical approaches, this paper aims to provide educators with practical strategies for integrating mass media into listening instruction.